(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In Decision-making domain, selection of best alternative is a complex problem based on someconflicting criteria. Multi Criteria Decision-Making (MCDM) makes it possible to find the best alternatives amongst all alternatives and to find the optimum solution. MCDM can be used across a wide range of application areas. The aim of the survey is mainly focused on different types of MCDM approach, which are robust and also optimal, to solve different real life problems. Analytical Hierarchical Process(AHP), Weighted Product Method(WPM), Ranking Organization method for Enrichment Evaluation (PROMETHEE), Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), Simple Additive Weighting(SAW), Elimination EtChoix Traduisant la REalite(ELECTRE), are various types of MCDM methods that we have discussed in this paper. This survey article contains various types of MCDM method and their applications on various domains and discussion about the advantage and disadvantage of each method